(untitled) (Patrimônio e Memória, 2020)
This article studies the Family Pact raised in 1831 by Lucas Alaman and its role in recovering the ideal of the Spanish-American union between the failure of the Congress of Panama in 1826 and the American Congress of Lima in 1847. It defends its relevance for a better understanding of the early stages of the Inter-American System, and the marke aspects of the Mexican defensive strategy on the eve of the North-American War of 1846- 1848.